1982
DOI: 10.1111/j.1476-5381.1982.tb09296.x
|View full text |Cite
|
Sign up to set email alerts
|

The EFFECTS OF MONOVALENT AND DIVALENT CATIONS ON THE Α‐ADRENOCEPTOR OF INTACT HUMAN PLATELETS

Abstract: 1 We have examined the effects of monovalent and divalent cations and purine nucleotides on the binding of agonists and antagonists to the x-adrenoceptor of intact human platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We are therefore at present unable to explain this phenomenon. yohimbine is significantly reduced by the presence of either cation both in intact platelets and in membrane preparations (Elliott & Grahame-Smith, 1982b;Daiguchi et al, 1981) whereas the affinity of [ 3H] -dihydroergocryptine is unaffected (Elliott & Grahame-Smith, 1982b;Tsai & Lefkowitz, 1979). Divalent cations also reduce the affinity of [ 3H] -yohimbine binding in rat cerebral cortex membranes (Cheung, Barnett & Nahorski, 1982), suggesting a generalized difference in the regulation of the binding sites for r3H1 -dihydroergocryptine and r3H]-yohimbine o n a2-adrenoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…We are therefore at present unable to explain this phenomenon. yohimbine is significantly reduced by the presence of either cation both in intact platelets and in membrane preparations (Elliott & Grahame-Smith, 1982b;Daiguchi et al, 1981) whereas the affinity of [ 3H] -dihydroergocryptine is unaffected (Elliott & Grahame-Smith, 1982b;Tsai & Lefkowitz, 1979). Divalent cations also reduce the affinity of [ 3H] -yohimbine binding in rat cerebral cortex membranes (Cheung, Barnett & Nahorski, 1982), suggesting a generalized difference in the regulation of the binding sites for r3H1 -dihydroergocryptine and r3H]-yohimbine o n a2-adrenoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…In the platelet lysate preparation the affinity of agonists has been shown to be sensitive to the presence of specific cations and purine nucleotides Michel, Hoffman & Lefkowitz, 1980). Studies in our laboratory suggest that similar factors may account for the low affinity of agonists on intact platelets (Elliott & Grahame-Smith, 1981). …”
Section: Specificity Ofthe [3h]-dihydroergocryptine Binding Sitementioning
confidence: 99%
“…It has been demonstrated that alpha2-adrenoceptors exist as a low affinity (a2L) state and a high affinity (a2H) state for agonists in broken cells, but the receptors in intact cells correspond to the a2L state (7). The present study was per formed to compare the affinities of DG-51 28 between the two affinity states of alpha2 adrenoceptors, in order to further clarify the binding properties of this antagonist.…”
mentioning
confidence: 99%